English Acquisition and Japanese Language Maintenance Among Japanese‐American Youth. (20th July 2009) - Kawamura, Sayaka; Goza, Franklin
Abstract: Despite the growing number of Japanese speaking immigrants in the United States and the pronounced linguistic dissimilarity between Japanese and English, few studies have examined English proficiency levels or Japanese language maintenance. We use 2000 data from the 5 per cent IPUMS file to examine English proficiency and language maintenance among first‐, second‐, and third‐or higher‐ generation Japanese immigrant youth in the United States. Before presenting multivariate results for our dependent variables, descriptive statistics are presented detailing numerous significant differences within and across generations. Furthermore, the second‐generation is divided into subgroups based on each parent's birthplace. This study also contrasts the results of Japanese‐Americans with those of Korean‐Americans, speakers of another language very distinct from English, in an attempt to ground the significance of our findings. Findings provide support for many of the hypotheses advanced. They also reveal that our regression models generally did a much better job explaining English acquisition among Japanese‐Americans than Korean‐Americans.